2011
DOI: 10.1007/s00011-011-0397-3
|View full text |Cite
|
Sign up to set email alerts
|

Associations between eNOS polymorphisms and susceptibility to systemic lupus erythematosus: a meta-analysis

Abstract: This meta-analysis of published studies shows that the 4b/a polymorphism may be associated with the development of LN, and the C786T polymorphism may be associated with SLE susceptibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
1
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 22 publications
(41 reference statements)
0
9
1
3
Order By: Relevance
“…Our findings contrast evidence found regarding other autoimmune diseases (26, 4448). For example, in the Spanish population, no association was found between FCRL3 rs11264799 and MS (44).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our findings contrast evidence found regarding other autoimmune diseases (26, 4448). For example, in the Spanish population, no association was found between FCRL3 rs11264799 and MS (44).…”
Section: Discussioncontrasting
confidence: 99%
“…In the Chinese population, a significant association was not found between TNFAIP3 rs10499194 and SLE (45); however, carriers of the CT genotype and combined TT/CT genotype had an increased risk for RA in the Chinese Han population (46). A recent meta-analysis revealed that there was no association between TNFAIP3 rs10499194 and RA in Europeans, but a significant association in Asians (OR = 1.254, 95% CI = 1.101–1.429, p  = 6.7 × 10 −4 ) (48). The discrepancies between our results and previous research may be attributed to differences in the populations and autoimmune diseases studied.…”
Section: Discussionmentioning
confidence: 99%
“…Because of its relationship with inflammation, several studies have investigated the association of eNOS gene polymorphisms with inflammatory rheumatic diseases, including rheumatoid arthritis, systemic lupus erythematosus, systemic sclerosis and Behcet's disease (11,12,17,23,24). Some of these studies have yielded evidence of an association of the eNOS polymorphisms with either the pathogenesis of rheumatic diseases or extraarticular manifestations (12,17,23,24).…”
Section: Discussionmentioning
confidence: 99%
“…Some of these studies have yielded evidence of an association of the eNOS polymorphisms with either the pathogenesis of rheumatic diseases or extraarticular manifestations (12,17,23,24). It is well known that there is a strong genetic basis for AS, and some genes, particularly HLAB27, have already been implicated in disease pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation